Treatment of Progressive Cherubism during the Second Dental Transitional Phase with Calcitonin - Ethan Meijer; Henk van den Berg; Arjen H. G. Cleven; Esther Edelenbos; Willem H. Schreuder (Hindawi Limited, 2023)
Cherubism is an autosomal dominant disease with variable expression. Aggressive forms of untreated cherubism may lead to severe malformation of the maxillofacial skeleton, developing tooth germs and teeth. Scarcely described and empirically applied interventional therapies during active stages of the disease try to limit the damage and deformation caused by progression of expanding intraosseous lesions. The final goal is to minimize the need for corrective surgeries once progressive growth has halted and disease enters its quiescent phase. New insights into the pathophysiology of cherubism hypothesize a potential role for dental development and jaw growth in the (hyper)activation of the disease. Theoretically, this could guide the ideal moment of pharmacological interventions. In this case report, the off-label use of systemic calcitonin treatment is described, stressing particularly the potential importance of its appropriate timing and duration of treatment.